HUBUNGAN PENERIMAAN DIRI DENGAN PENALARAN MORAL PADA PENGHUNI LEMBAGA PEMASYARAKATAN ANAK DI BLITAR - Yeni Kukuh Herminingsih; Yumei Astutik (University of Merdeka Malang, 2013)
The study was conducted to determine the relationship between self-acceptance with moral reasoning at occupants of child penitentiary in Blitar. The populations in this study were in Blitar of 245 people. The samples in this study were occupants of child penitentiary in Blitar who continue junior high school education in penitentiary as many as 30 people. The sample was purposive sampling technique. The process of data analysis used was correlation product moment. Results for self-acceptance scale 70 items made as many as 33 valid items. The self-acceptance reliability calculation give coefficient value 0.722 where that number according to reliability norm stated as reliable self-acceptance variable. The results of data analysis showed that calculated r bigger than r table (- 0.411 0.361) with a significance level of 0,05, which indicates that there is a negative relationship between self-acceptance with moral reasoning, so that the working hypothesis (Ha) which states there is a relationship between self-acceptance with moral reasoning, acceptable.